Solutions of the system of functional equations f(x o y) = f(x)g(y) + g(x)f(y) and g(x o y) = g(x)g(y) - f(x)f(y) on semigroups - Kanokporn Palasri (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 1999